Unmet need for contraception and its associated factors among women in Papua New Guinea: analysis from the demographic and health survey - Amma Kyewaa Agyekum; Kenneth Setorwu Adde; Richard Gyan Aboagye; Tarif Salihu; Abdul-Aziz Seidu; Bright Opoku Ahinkorah (BMC, 2022)
Plain language summary Unmet need for contraception is highest in low-and middle-income countries. This study investigates the prevalence and correlates of unmet need for contraception among women in Papua New Guinea. We extracted data from the most recent Demographic and Health Survey conducted in Papua New Guinea. Our study involved 7950 women with diverse contraceptive needs and those who have complete data on all variables of interest. We found that the overall unmet need for contraception was 32.2%. Marital status, parity, decision maker on respondent's healthcare, wealth status, and region were found to have a significant relationship with unmet need for contraception. Cohabiting women recorded a higher likelihood for unmet need for contraception as compared to those married. Women with at least on child showed greater probability of unmet contraceptive need relative to women without children. Likewise, a higher probability of unmet need was found among women whose partners decided on their healthcare as compared to those who decided on their own healthcare. With regards to wealth, the likelihood of unmet contraceptive need decreased with an increase in wealth status. With region, it was found that women in the Mamose region had greater likelihood of unmet contraceptive need compared to those in Southern region. Interventions aimed at reducing unmet need for contraception should be implemented taking into consideration significant socio-demographic characteristics of women as identified in this study.